(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Drug addiction is a social curse involving all classes of people for ages. Not only it increases individuals morbidity and mortality but also creates social unrest and reduces the national productivity frequent assessment surveys have provided insights into the pattern and required responses. Objectives: To assess the sociodemographic profile of drug addicts admitted in a prominent drugs deaddiction centre of Dhaka, Bangladesh. Materials and Methods: This cross-sectional descriptive study carried out on 158 admitted patients in Thikana Psychiatric/ Drug de-addiction clinic, from October 2014 to September 2015. A predesigned questionnaire used in evaluating the patients by two or more sittings face-to-face interviews. Results: Amongst 158 patients, 94.30% were male and 62.0% were in the age group of 21-30 years with a mean age of 26.46 + 6.168 years. Majority (60.8%) patients were married and 48.7% had education up to higher secondary level, 29.1% were unemployed and 27.2% students. About 36.7% were spending between 101- 500 Taka/day and 65.8% arrange money for drugs by themselves. The reason behind starting drug abuse was mainly peer pressure (49.4%) followed by curiosity (26.6%). The mean age of starting drug was 19.42 + 7.68 years and 68.35% were addicted to the drug for the period between 1-5 years. Only 4.4% had positive family history of drug abuse. Regarding route of drug abuse, ingestion was most popular (55.1%) and only 8.9% participants were using injectable route. Amongst abused drugs, Amphetamine (Yaba) was most popular among the female (77.7%) and students (21.5%). Conclusion: Drug abuse cripples the individual, the family, the society and finally the nation. Since younger generations most affected by the drug abuse, it is prudent to evolve and apply preventive, curative and rehabilitative strategies before it is too late. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 113-115